Exploring Positive School Attributes: Evidence From School Leader and Teacher Perspectives - Avinash Auliah (SAGE Publishing, 2021)
The extent to which school stakeholders perceive positive school attributes remains unclear in the literature. This study seeks to provide an understanding of positive school attributes from the school leaders and teachers’ perspectives in the Malaysian school context. This study employed a qualitative case study research design with 14 informants selected from seven Malaysian secondary schools. The thematic analysis informed six emerging themes: (1) stimulating positive emotion, (2) promoting positive engagement, (3) fostering positive relationships, (4) cultivating positive meaning, (5) nurturing positive accomplishment, and (6) cultivating spirituality in expressing positive school attributes. Fostering positive relationships were specified as (1) teacher-teacher relationship, (2) teacher-student relationship, and (3) student-student relationship. Cultivating spirituality is a newly emerged theme that is added to the unique positive school attributes. These newly added components of the existing PERMA model can trigger further research in positive education studies.